THE INFLUENCE OF LOCUS OF CONTROL, LIFESTYLE, AND FINANCIAL SOCIALIZATION, ON FINANCIAL MANAGEMENT BEHAVIOR IN SHOPEE PAYLATER USER STUDENTS - Wahyu Wigati; Haryati Setyorini (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
The younger generation, including university students, is a generation that is not good at managing their finances. This is because today's young generation has a different lifestyle from previous generations. This generation tends to have a more extravagant lifestyle and find it difficult to save. This habit will certainly result in financial risks that will be faced in the future, due to poor financial management. So that this research aims to see how the influence of locus of control on the financial management behavior of student users of Shopee paylater. The influence of lifestyle on the financial management behavior of Shopee paylater user students. As well as the influence of financial socialization on the financial management behavior of student users of Shopee paylater. The object of this research is students in the city of Surabaya with a sample size of 101 respondents. The sample was obtained using purposive sampling method. The data analysis technique used is multiple linear regression. The first result obtained is that there is a significant positive effect of locus of control on financial management behavior. The second result obtained is that there is no significant effect of lifestyle on financial management behavior. And the third result obtained is that there is no significant effect of financial socialization on financial management behavior